(untitled) (Scientific journal of the Fergana State University, 2026)
The article presents information on traditional methods of calculating the population density of a region, which are widely used in practice. Based on the analysis of the regions of the republic, the traditional methods used in practice are explained. In addition, the weaknesses of traditional methods are described. The topic of the article is revealed using examples of social population density, which allows us to reveal the content of the traditional method. The average population density, its role in the economy, taking into account the territorial differences of the Samarkand region, is also explained and considered.